TGF‐β superfamily co‐receptors in cancer. Issue 1 (9th April 2021) - Pawlak, John B.; Blobe, Gerard C.
Abstract: Transforming growth factor‐β (TGF‐β) superfamily signaling via their cognate receptors is frequently modified by TGF‐β superfamily co‐receptors. Signaling through SMAD‐mediated pathways may be enhanced or depressed depending on the specific co‐receptor and cell context. This dynamic effect on signaling is further modified by the release of many of the co‐receptors from the membrane to generate soluble forms that are often antagonistic to the membrane‐bound receptors. The co‐receptors discussed here include TβRIII (betaglycan), endoglin, BAMBI, CD109, SCUBE proteins, neuropilins, Cripto‐1, MuSK, and RGMs. Dysregulation of these co‐receptors can lead to altered TGF‐β superfamily signaling that contributes to the pathophysiology of many cancers through regulation of growth, metastatic potential, and the tumor microenvironment. Here we describe the role of several TGF‐β superfamily co‐receptors on TGF‐β superfamily signaling and the impact on cellular and physiological functions with a particular focus on cancer, including a discussion on recent pharmacological advances and potential clinical applications targeting these co‐receptors. Key Findings: TGF‐β superfamily co‐receptors primarily modify ligand interactions with their cognate receptor complexes to enhance or suppress downstream SMAD signaling. Many TGF‐β superfamily co‐receptors are secreted or shed from the cell surface to further modify surface receptor signaling via ligand sequestration. Dysregulation of TGF‐β superfamily co‐receptors contribute to the pathophysiology of many cancers and a rational for the pharmacological targeting of these co‐receptors is on the rise.